Assessment of frailty, daily life activities, and nutrition of elderly immigrants: A household based cross-sectional study - De?er, Mehmet Sait; Sezerol, Mehmet Akif; Atak, Muhammed (My University, 2024)
With the global migrant population on the rise, it's imperative to focus on the health status of more vulnerable groups within these communities. The elderly immigrants face myriad physical and psychosocial challenges that significantly impact their health and quality of life. This study aims to investigate the nutrition, daily life activities, and clinical frailty status of elderly immigrants residing in Türkiye. A cross-sectional design was employed in the Sultanbeyli District, focusing on Syrian immigrants aged 65 and over. Participants were surveyed face-to-face by interpreters proficient in Arabic. The questionnaire comprised sociodemographic details, health status, and scales like Katz Daily Life Activities, Clinical Frailty, and Mini Nutritional Assessment. The data analysis was executed using SPSS 22. Continuous variables were presented as mean?±?standard deviation (SD) and median, while categorical ones were expressed in numbers and percentages (%). A significance level of P <.05 was considered for the analyses. The average age of the participants was determined as 71.64?±?6.20 years. In the study group, 49.7% were female, 75.5% were younger than 75 years old, 47.7% had less than primary school education, 56.3% were married, 42.4% had a low income level, and 56.9% lived in the same household with 5 or more people. Among the participants in the study group, 47% had walking and balance problems, 29.1% had a history of falls in the last year, 10.6% were disabled, 69.5% complained of pain, 82.8% had a chronic illness, and 43% had polypharmacy. The median value of the KATZ Daily Living Activities scale was 6, the mean score of the Clinical Frailty Score scale was 3.25?±?1.25, and the mean score of the Mini Nutritional Assessment scale was 12.40?±?2.15. Among immigrant elderly individuals, 88.1% were able to sustain their lives independently, 13.9% were clinically frail, and 3.3% were at risk of malnutrition. Factors such as age, level of education, socioeconomic status, marital status, number of cohabitants in the household, BMI, neurological problems, walking-balance disorders, disability, and presence of chronic diseases are associated with daily life activities, frailty, and malnutrition status. It is believed that broader field research with greater participation would be beneficial for evaluating the nutritional status of immigrant elderly individuals.
Keywords: Clinical Frailty; Daily Life Activities; Elderly; Immigrant; Katz; Mini Nutritional Assessment; Nutrition